The viability of digital and rapid prototyping in enhancing ceramics product development - Olalere, Folasayo Enoch; Ab. Aziz Shuaib (2013)
This research practically investigates on how to reduce development time, development cost and also improve prototype quality in ceramic production. The researcher used an experimental approach, by first investigating and analysing the conventional method used by ceramics manufacturers in product development. This was achieved with several visits to three ceramic factories in Kelantan, Malaysia. After which a digital method was developed by introducing computer-aided design (CAD) into three stages in development process. In order to test the viability of the CAD introduced, the digital method was used to develop prototypes of ceramic products selected from the three ceramic factories. Finally, a comparison was done between conventional and digital method based on development time, development cost and prototype quality. This reveals that digital method can successfully reduce development time and improve prototype quality in ceramic product development process. However, the comparison also reveals that digital method is more expensive than the conventional method used by the factories in ceramic product development.